Miracle in Rajasthan: Traditional Practice of Rainwater Harvesting - Thanju, Jeevan P.; Shrestha, Basanta D (Hydro Nepal: Journal of Water, Energy and Environment, 2011)
Paper report. DOI: 10.3126/hn.v7i0.4229 Hydro Nepal Journal of Water, Energy and Environment Vol 7, July, 2010 Page: 20-22 Uploaded date: 31 January, 2011